Independent Curriculum Assessment and Evaluation in History Learning in Public High Schools throughout Barito Kuala Regency - Sriwati; Wisnu Subroto; Melisa Prawitasari; Fitri Mardiani (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
This research uses a qualitative approach. Data collection and data sources were determined by purposive sampling. Data collection techniques were carried out using observation, interviews and documentation. Data analysis techniques are carried out through data collection, reduction, presentation and conclusion. Then, to obtain the validity of the data in this research, the researcher used triangulation techniques. The research results show that the State High School in Barito Kuala has implemented an independent curriculum. Learning and assessment have been carried out in an integrated manner. In history learning, teachers use assessments to measure the achievement of learning objectives. Three types of assessments are used: diagnostic, formative, and summative. The assessment results are used as a basis for assessing students' cognitive, affective, and psychomotor aspects, as well as reflective material for teachers to use in determining subsequent learning strategies.